2021
DOI: 10.1513/annalsats.202010-1311oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Critical Care Occupancy and Outcomes of Critically Ill Patients during the 2020 COVID-19 Winter Surge and 2009 H1N1 Influenza Pandemic in Australia

Abstract: Availability of data and material and code availability: A de-identified dataset will be made available upon request to the corresponding authors one year after the publication of this study. The request must include a statistical analysis plan. The code is available upon request.Author's Contributions: All authors designed the study and were involved in collecting the data with the help of the study collaborators. Dr. Serpa Neto did the analyses. Drs. Serpa Neto, Burrell, Bailey, Cooper, Bellomo and Udy draft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 15 publications
7
29
1
Order By: Relevance
“…This is consistent with previously published data that a higher proportion of patients with COVID-19 required intensive care and mechanical ventilation than those with in uenza, with an increased risk of developing extra pulmonary organ dysfunction [11,15,16]. In contrast, an Australian study comparing COVID-19 patients with H1N1 in uenza pandemic in 2009, concluded that fewer proportions of COVID-19 admissions needed invasive mechanical ventilation [12]. This is likely due to the re ection of variations in pandemic severity and utilisation of ICU healthcare between countries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with previously published data that a higher proportion of patients with COVID-19 required intensive care and mechanical ventilation than those with in uenza, with an increased risk of developing extra pulmonary organ dysfunction [11,15,16]. In contrast, an Australian study comparing COVID-19 patients with H1N1 in uenza pandemic in 2009, concluded that fewer proportions of COVID-19 admissions needed invasive mechanical ventilation [12]. This is likely due to the re ection of variations in pandemic severity and utilisation of ICU healthcare between countries.…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of these differences, the ICU, hospital and 28-day mortality was similar between both groups. Our nding of similar mortality is consistent with a large multicentre study comparing critically ill COVID-19 with H1N1 in uenza pandemic during 2009 [12]. Our overall mortality is lower than previously published national and international data sets [2,13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study by Neto and colleagues ( 1 ) compared critical care bed occupancy and outcomes of critically ill patients during the coronavirus disease (COVID-19) pandemic with the 2009 H1N1 influenza pandemic in Australian intensive care units (ICUs). The study showed that the patients with COVID-19 had similar unadjusted mortality (11.5% in COVID-19 vs. 16.1% in H1N1; P = 0.10) and a lower adjusted risk of death in patients with COVID-19 (odds ratio, 0.46 [95% confidence interval, 0.25–0.84]; P = 0.01).…”
mentioning
confidence: 99%
“…The policy of early ICU admissions during the COVID-19 pandemic was reflected by the lower acuity of patients with COVID-19 as evidenced by lower acute physiologic assessment and chronic health evaluation score and lower need for invasive mechanical ventilation. Such lower acuity of patients led to lower mortality and shorter ICU length of stay in patients with COVID-19 ( 1 ). The ICU length of stay is significantly affected by the availability of hospital ward beds ( 6 ).…”
mentioning
confidence: 99%